Joint arterial input function and tracer kinetic parameter estimation from undersampled dynamic contrast‐enhanced MRI using a model consistency constraint. Issue 5 (14th September 2017) - Guo, Yi; Lingala, Sajan Goud; Bliesener, Yannick; Lebel, R. Marc; Zhu, Yinghua; Nayak, Krishna S.
Abstract : Purpose: To develop and evaluate a model‐based reconstruction framework for joint arterial input function (AIF) and kinetic parameter estimation from undersampled brain tumor dynamic contrast‐enhanced MRI (DCE‐MRI) data. Methods: The proposed method poses the tracer‐kinetic (TK) model as a model consistency constraint, enabling the flexible inclusion of different TK models and TK solvers, and the joint estimation of the AIF. The proposed method is evaluated using an anatomic realistic digital reference object (DRO), and nine retrospectively down‐sampled brain tumor DCE‐MRI datasets. We also demonstrate application to 30‐fold prospectively undersampled brain tumor DCE‐MRI. Results: In DRO studies with up to 60‐fold undersampling, the proposed method provided TK maps with low error that were comparable to fully sampled data and were demonstrated to be compatible with a third‐party TK solver. In retrospective undersampling studies, this method provided patient‐specific AIF with normalized root mean‐squared‐error (normalized by the 90th percentile value) less than 8% at up to 100‐fold undersampling. In the 30‐fold undersampled prospective study, the proposed method provided high‐resolution whole‐brain TK maps and patient‐specific AIF. Conclusion: The proposed model‐based DCE‐MRI reconstruction enables the use of different TK solvers with a model consistency constraint and enables joint estimation of patient‐specific AIF. TK maps and patient‐specific AIF with high fidelity can be reconstructed at up to 100‐fold undersampling in k, t‐space. Magn Reson Med 79:2804–2815, 2018. © 2017 International Society for Magnetic Resonance in Medicine.